Nivolumab, nivolumab–ipilimumab, and VEGFR-tyrosine kinase inhibitors as first-line treatment for metastatic clear-cell renal cell carcinoma (BIONIKK): a biomarker-driven, open-label, non-comparative, randomised, phase 2 trial. Issue 5 (May 2022) - Vano, Yann-Alexandre; Elaidi, Réza; Bennamoun, Mostefa; Chevreau, Christine; Borchiellini, Delphine; Pannier, Diane; Maillet, Denis; Gross-Goupil, Marine; Tournigand, Christophe; Laguerre, Brigitte; Barthélémy, Philippe; Coquan, Elodie; et al.
Summary: Background: We previously reported a 35-gene expression classifier identifying four clear-cell renal cell carcinoma groups (ccrcc1 to ccrcc4) with different tumour microenvironments and sensitivities to sunitinib in metastatic clear-cell renal cell carcinoma. Efficacy profiles might differ with nivolumab and nivolumab–ipilimumab. We therefore aimed to evaluate treatment efficacy and tolerability of nivolumab, nivolumab–ipilimumab, and VEGFR-tyrosine kinase inhibitors (VEGFR-TKIs) in patients according to tumour molecular groups. Methods: This biomarker-driven, open-label, non-comparative, randomised, phase 2 trial included patients from 15 university hospitals or expert cancer centres in France. Eligible patients were aged 18 years or older, had an Eastern Cooperative Oncology Group performance status of 0–2, and had previously untreated metastatic clear-cell renal cell carcinoma. Patients were randomly assigned (1:1) using permuted blocks of varying sizes to receive either nivolumab or nivolumab–ipilimumab (ccrcc1 and ccrcc4 groups), or either a VEGFR-TKI or nivolumab–ipilimumab (ccrcc2 and ccrcc3 groups). Patients assigned to nivolumab–ipilimumab received intravenous nivolumab 3 mg/kg plus ipilimumab 1 mg/kg every 3 weeks for four doses followed by intravenous nivolumab 240 mg every 2 weeks. Patients assigned to nivolumab received intravenous nivolumab 240 mg every 2 weeks. Patients assigned to VEGFR-TKIs received oral sunitinib (50 mg/day for 4 weeks every 6 weeks) or oral pazopanib (800 mg daily continuously). The primary endpoint was the objective response rate by investigator assessment per Response Evaluation Criteria in Solid Tumors version 1.1. The primary endpoint and safety were assessed in the population who received at least one dose of study drug. This trial is registered with ClinicalTrials.gov, NCT02960906, and with the EU Clinical Trials Register, EudraCT 2016-003099-28, and is closed to enrolment. Findings: Between June 28, 2017, and July 18, 2019, 303 patients were screened for eligibility, 202 of whom were randomly assigned to treatment (61 to nivolumab, 101 to nivolumab–ipilimumab, 40 to a VEGFR-TKI). In the nivolumab group, two patients were excluded due to a serious adverse event before the first study dose and one patient was excluded from analyses due to incorrect diagnosis. Median follow-up was 18·0 months (IQR 17·6–18·4). In the ccrcc1 group, objective responses were seen in 12 (29%; 95% CI 16–45) of 42 patients with nivolumab and 16 (39%; 24–55) of 41 patients with nivolumab–ipilimumab (odds ratio [OR] 0·63 [95% CI 0·25–1·56]). In the ccrcc4 group, objective responses were seen in seven (44%; 95% CI 20–70) of 16 patients with nivolumab and nine (50% 26–74) of 18 patients with nivolumab–ipilimumab (OR 0·78 [95% CI 0·20–3·01]). In the ccrcc2 group, objective responses were seen in 18 (50%; 95% CI 33–67) of 36 patients with a VEGFR-TKI and 19 (51%; 34–68) of 37 patients with nivolumab–ipilimumab (OR 0·95 [95% CI 0·38–2·37]). In the ccrcc3 group, no objective responses were seen in the four patients who received a VEGFR-TKI, and in one (20%; 95% CI 1–72) of five patients who received nivolumab–ipilimumab. The most common treatment-related grade 3–4 adverse events were hepatic failure and lipase increase (two [3%] of 58 for both) with nivolumab, lipase increase and hepatobiliary disorders (six [6%] of 101 for both) with nivolumab–ipilimumab, and hypertension (six [15%] of 40) with a VEGFR-TKI. Serious treatment-related adverse events occurred in two (3%) patients in the nivolumab group, 38 (38%) in the nivolumab–ipilimumab group, and ten (25%) patients in the VEGFR-TKI group. Three deaths were treatment-related: one due to fulminant hepatitis with nivolumab–ipilimumab, one death from heart failure with sunitinib, and one due to thrombotic microangiopathy with sunitinib. Interpretation: We demonstrate the feasibility and positive effect of a prospective patient selection based on tumour molecular phenotype to choose the most efficacious treatment between nivolumab with or without ipilimumab and a VEGFR-TKI in the first-line treatment of metastatic clear-cell renal cell carcinoma. Funding: Bristol Myers Squibb, ARTIC.